APPLYING MULTI- LEVEL ANTCOLONY OPTIMIZATION TO RESTRICTED FOREST - Prashant Kumar (International Journal of Multidisciplinary Research and Studies, 2020)
Since the beginning of the last century, one of the most important concerns has been the problems arising from the planning of forest transport. Off-road activities are those that involve the transportation of wood from stump locations to roadside landings or landings in centralized locations. The term "on-road activities" refers to the process of transporting timber to its final destinations using land-based vehicles. The exact algorithm and approximation algorithm, both are different methods that have been used in the process of solving ftpp. The core of approximation algorithms commonly referred to as heuristics is the process of ranking a large number of possible answers and choosing the most appropriate one. The fact that exact algorithms can generate optimal answers is the most important advantage associated with using them.